2008
DOI: 10.1183/09031936.00109007
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial class is not obviously important in outpatient pneumonia: a meta-analysis

Abstract: The aim of the present study was to systematically compare outcomes between antibiotic classes in treating outpatient community-acquired pneumonia, with regard to antibacterials active against atypical organisms, as well as between various antibacterial classes with similar atypical coverage.A meta-analysis was performed on randomised controlled trials of antibacterials for community-acquired pneumonia in outpatients aged ≥18 yrs. The studies were independently reviewed by two reviewers. Clinical success and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
1
7
0
9
Order By: Relevance
“…However, the need for empiric treatment of these organisms in mild CAP in the outpatient setting has been challenged as evidence suggests no benefit of covering these organisms with appropriate antibiotics in the outpatient setting. [90162163170176177] Combination therapy should be restricted to patients with severe pneumonia. [103120] Its advantages include expansion of the antimicrobial spectrum to include atypical pathogens and possibly immunomodulation.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…However, the need for empiric treatment of these organisms in mild CAP in the outpatient setting has been challenged as evidence suggests no benefit of covering these organisms with appropriate antibiotics in the outpatient setting. [90162163170176177] Combination therapy should be restricted to patients with severe pneumonia. [103120] Its advantages include expansion of the antimicrobial spectrum to include atypical pathogens and possibly immunomodulation.…”
Section: Community-acquired Pneumoniamentioning
confidence: 99%
“…The review by Mills et al [38] showed similar resultsthat is, no improvement in clinical outcome with the use of antibiotics active against atypical pathogens, except among the subset of patients infected with L. pneumophila (table 2). The most recent report [37] reviewed studies from 1966 through July 2007 involving outpatients with CAP and concluded that there was no advantage to using specific antibacterials for treatment of mild CAP in otherwise healthy outpatients. A potential concern about these reports is that they tended to analyze the same studies.…”
Section: Is It Necessary To Treat For Atypical Pathogens In Cap?mentioning
confidence: 96%
“…On the basis of a literature review, there have been 3 metaanalyses performed to address this issue [36][37][38]. All 3 used the same study format with a review of comparative trials of agents showing activity against atypical pathogens (macrolides, fluoroquinolones, or tetracyclines) versus b-lactams.…”
Section: Is It Necessary To Treat For Atypical Pathogens In Cap?mentioning
confidence: 99%
“…Однако значение этого феномена дискутабельно, более того, известно, что препараты, неактивные против атипичной микрофлоры (ингибиторзащи щенные аминопенициллины, цефалоспорины III по коления), эффективно элиминируя гемофильную инфекцию [34][35][36], быстро купируют обострение и обеспечивают более продолжительный период без обострений, чем, например, неактивные против ге мофильной палочки макролиды [34][35][36][37]. Эффектив ность β лактамов при атипичной инфекции, в част ности микоплазменной, отмечена в клинических исследованиях и метаанализах [38][39][40].…”
Section: этиология обострений хоблunclassified